Impact of social media on health education actions for the population (Research, Society and Development, 2021)
Objectives: To analyze the impact of social media for health education for the population. Methodology: This is an integrative literature review, carried out from October to December 2020, following the six steps indicated for the integrative review, the guiding question was defined based on the acronym PICo. The following databases were used: Latin American and Caribbean Literature in Health Sciences (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE) via PubMed, Nursing Database (BDENF) and Bibliographic Index Español en Ciencias de la Salud. Results: Studies reveal that Information and Communication Technologies (ICT) have been gaining more and more support and credit in the proliferation of content, in view of the accessibility of a large part of the population, generating valuation and development of innovative methodologies. It is also becoming very important in the academic field, destroying barriers, promoting the spread of knowledge. Final considerations: Based on the results, it is observed that the use of technology, and especially of digital media, for the insertion of the population in the construction of their own knowledge has great value and credibility, because in this way, the information can be passed on more quickly and efficiently to the population.